Contract documents for supply, installation, testing and commissioning of lift & escalator for Brac University new campus project at holding no. Kha 224, Merul Badda, Dhaka -1212, Bangladesh. - Brac University (Brac University, 2023)
This agreement made between Brac University and Edgework Limited to supply, installation, testing and commissioning of lift & escalator for Brac University new campus project.